2022
DOI: 10.1038/s41598-022-27009-w
|View full text |Cite
|
Sign up to set email alerts
|

Biases in human perception of facial age are present and more exaggerated in current AI technology

Abstract: Our estimates of a person’s age from their facial appearance suffer from several well-known biases and inaccuracies. Typically, for example, we tend to overestimate the age of smiling faces compared to those with a neutral expression, and the accuracy of our estimates decreases for older faces. The growing interest in age estimation using artificial intelligence (AI) technology raises the question of how AI compares to human performance and whether it suffers from the same biases. Here, we compared human perfo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 31 publications
0
2
0
Order By: Relevance
“…For instance, although artificial intelligence (AI) technology can deliver comprehensive characteristics of facial aging, it has not been widely used owing to considerable errors and biases. 31 , 32 The use of questionnaire-based tools can help overcome the challenges associated with facial aging assessment. 33 The large sample size of the IEU OpenGWAS project may alleviate concerns about measurement errors when evaluating facial skin aging using questionnaires, highlighting the benefits of such data.…”
Section: Discussionmentioning
confidence: 99%
“…For instance, although artificial intelligence (AI) technology can deliver comprehensive characteristics of facial aging, it has not been widely used owing to considerable errors and biases. 31 , 32 The use of questionnaire-based tools can help overcome the challenges associated with facial aging assessment. 33 The large sample size of the IEU OpenGWAS project may alleviate concerns about measurement errors when evaluating facial skin aging using questionnaires, highlighting the benefits of such data.…”
Section: Discussionmentioning
confidence: 99%
“…First, many of these types of bias (racism, sexism, and ageism) have their roots in similar problems, such as underrepresentation [4,9]. For example, a 2022 study of 21 age-recognition systems found that artificial intelligence systems consistently identified age with less accuracy across all age, gender, and ethnic categories, which the authors speculated was due to older adults being underrepresented in training data [49]. Second, the methods used to balance age-related bias in these papers may also have applications for other types of bias.…”
Section: Overviewmentioning
confidence: 99%
“…Clear annotation manuals with straightforward and transparent instructions are essential to reach valid and unbiased conclusions. A study by Ganel et al [79] showed that the bias related to human assessment is transferable to AI algorithms for automated age prediction, causing poor performance.…”
Section: Label Biasmentioning
confidence: 99%